Covalent cofactor attachment to proteins: cytochrome c biogenesis. (1st August 2005) - Stevens, J.M.; Uchida, T.; Daltrop, O.; Ferguson, S.J.
Abstract : Haem (Fe-protoporphyrin IX) is a cofactor found in a wide variety of proteins. It confers diverse functions, including electron transfer, the binding and sensing of gases, and many types of catalysis. The majority of cofactors are non-covalently attached to proteins. There are, however, some proteins in which the cofactor binds covalently and one of the major protein classes characterized by covalent cofactor attachment is the c -type cytochromes. The characteristic haem-binding mode of c -type cytochromes requires the formation of two covalent bonds between two cysteine residues in the protein and the two vinyl groups of haem. Haem attachment is a complex post-translational process that, in bacteria such as Escherichia coli, occurs in the periplasmic space and involves the participation of many proteins. Unexpectedly, it has been found that the haem chaperone CcmE (c ytochrome c m aturation), which is an essential intermediate in the process, also binds haem covalently before transferring the haem to apocytochromes. A single covalent bond is involved and occurs between a haem vinyl group and a histidine residue of CcmE. Several in vitro and in vivo studies have provided insight into the function of this protein and into the overall process of cytochrome c biogenesis.